The AI (R)evolution ... - Russ-Smith, Jessica; Lazarus, Michelle (Monash University, 2025)
How can we walk along the path already led by First Nations communities to generate technology that is supportive of, and not at odds with, all life? AI has quickly become embedded in our daily lives and ways of working, from healthcare to classrooms to government services. What future are we creating – and what questions should we be asking about it now?Associate Professor Jessica Russ-Smith and Professor Michelle D. Lazarus explore a series of compelling topics about moving through a world dominated by data and algorithms, such as: how can we embed First Nations knowledges into AI datasets? Who is benefitting from an AI-driven future, and whose ethics are we considering? Does AI help or hinder us in addressing contemporary challenges such as climate change?The AI revolution is ours to shape. Will we place humanity, and the values of social justice and equity, at its core, or will we allow it to enforce entrenched patterns of bias and power inequalities? Let’s stand up for our own future.Published October ...